Exercice 8.5: idem ex. 8.4 Terminé

Consigne

Mêmes questions, en remplaçant la ligne :
T(k, m) ← k + m

par

T(k, m) ← 2 * k + (m + 1)
puis par :
T(k, m) ← (k + 1) + 4 * m

Pseudo code

Tableau T(3, 1) en ENTIER
Variables k, m, en ENTIER
DEBUT
POUR k ← 0 à 3
  POUR m ← 0 à 1
    // Premier remplacement
    T(k, m) ← 2 * k + (m + 1)

    // Deuxième remplacement
    T(k, m) ← (k + 1) + 4 * m
  m SUIVANT
k SUIVANT

POUR k ← 0 à 3
  POUR m ← 0 à 1
    ECRIRE T(k, m)
  m SUIVANT
k SUIVANT
FIN

Réponse

// Premier remplacement
> T(k, m) ← 2 * k + (m + 1)
(k vaut 0)
T[0][0] = (2x0) + (0+1) = 0 + 1 = 1
T[0][1] = (2x0) + (1+1) = 0 + 2 = 2

(k vaut 1)
T[1][0] = (2x1) + (0+1) = 2 + 1 = 3
T[1][1] = (2x1) + (1+1) = 2 + 2 = 4

(k vaut 2)
T[2][0] = (2x2) + (0+1) = 4 + 1 = 5
T[2][1] = (2x2) + (1+1) = 4 + 2 = 6

(k vaut 3)
T[3][0] = (2x3) + (0+1) = 6 + 1 = 7
T[3][1] = (2x3) + (1+1) = 6 + 2 = 8

// Deuxième remplacement
> T(k, m) ← (k + 1) + 4 * m
(k vaut 0)
T[0][0] = (0+1) + (4x0) = 1 + 0 = 1
T[0][1] = (0+1) + (4x1) = 1 + 4 = 5

(k vaut 1)
T[1][0] = (1+1) + (4x0) = 2 + 0 = 2
T[1][1] = (1+1) + (4x1) = 2 + 4 = 6

(k vaut 2)
T[2][0] = (2+1) + (4x0) = 3 + 0 = 3
T[2][1] = (2+1) + (4x1) = 3 + 4 = 7

(k vaut 3)
T[3][0] = (3+1) + (4x0) = 4 + 0 = 4
T[3][1] = (3+1) + (4x1) = 4 + 4 = 8